Antioxidant Profile of Velvet Bean and Jack Bean and The Effect of Processing Towards Its Value – A Review - Steffi Agustine Chandra; Christiana Retnaningsih; Alberta Rika Pratiwi (Soegijapranata Catholic University, 2025)
Velvet bean (Mucuna pruriens) and jack bean (Canavalia ensiformis) are members of legumes that are found in tropical area including Indonesia, that contains high nutritional and functional values but still haven’t been deeply explored. Both velvet bean and jack bean were reported to contain antioxidant capacities, which are mainly affected by its flavonoid, polyphenol, and tannin contents. L-DOPA, a non-protein amino acid compound, was also reported as the dominant compound in velvet bean that exhibit bioactive capacities. On the other hand, kaempferol was reported as the dominant flavonoid compound in jack bean. These bioactive compounds present in velvet bean and jack bean ant their antioxidant capacities can be affected by processing treatment they’re subjected into, and thus, it is important to understand and put into considerations how different processing treatments may affect the antioxidant profile and capacity of velvet bean and jack bean while producing functional food based on these food sources. The objective of this review is to highlight the antioxidant profile of the seeds of velvet bean and jack bean as well as the effect of processing treatments towards its value.